Sex cord-like elements in Müllerian lesions: Report of two rare cases and review of the literature - Yildiz, Bahadir; Zhang, Huina; McDowell, Jamie Linn; Katerji, Hani; Varghese, Sharlin; Wang, Xi (Human Pathology Reports, 2025)
Sex cord-like elements (SCLEs) are uncommon in non-ovarian sex cord lesions in the female genital tract and are most commonly observed in uterine endometrial stromal tumors (EST) and uterine tumors resembling ovarian sex cord tumors (UTROSCT). Here, we describe two rare cases harboring SCLEs. The first case was a 72-year-old female with postmenopausal bleeding. Endometrial curettage showed endometrial polyps with SCLEs, confirmed by immunohistochemical staining for calretinin, Melan A, and inhibin. The second case was a 71-year-old female with a complex cystic and solid mass in the left ovary, and bilateral salpingo-oophorectomy revealed an ovarian adenosarcoma with extensive SCLEs. Both patients recovered well and the presence of SCLEs did not change the fate of the parent lesions. Our report highlights the importance of awareness of SCLEs in these Müllerian lesions, although exceedingly rare, to avoid diagnostic confusion.